PERHITUNGAN PEMOTONGAN PPh 21 PADA KARYAWAN KOPERASI JASA DIRGAHAYU MAJU SEJAHTERA DI SAMARINDA MENURUT UNDANG-UNDANG NOMOR 36 TAHUN 2008 - Eka Yudhyani, Kristina Ugan LCA Robin Jonathan (EKONOMIA, 2015)
The legal basis for calculation and withholding of Article 21 is the Income Tax Act No. 36 of 2008 and the Regulation of the Minister of Finance No. 162 / PMK.011 / 2012, of the Guidelines calculation and withholding of Article 21.Problem Formulation of this research is